Venus Kinase Receptors: Prospects in Signaling and Biological Functions of These Invertebrate Kinases - Dissous, Colette; Morel, Marion; Vanderstraete, Mathieu (Frontiers in Endocrinology, 2014)
Venus Kinase Receptors (VKRs) form a family of invertebrate receptor tyrosine kinases (RTKs) initially discovered in the parasitic platyhelminth Schistosoma mansoni. VKRs are single transmembrane receptors which contain an extracellular Venus Flytrap (VFT) structure similar to the ligand binding domain of G Protein Coupled Receptors of class C, and an intracellular Tyrosine Kinase domain close to that of Insulin Receptors. VKRs are found in a large variety of invertebrates from cnidarians to echinoderms, and are highly expressed in larval stages and in gonads, suggesting a role of these proteins in embryonic and larval development as well as in reproduction. Vkr gene silencing could demonstrate the function of these receptors in oogenesis as well as in spermatogenesis in Schistosoma .mansoni. VKRs are activated by amino-acids, and highly responsive to arginine. As many other RTKs, they form dimers when activated by ligands and induce intracellular pathways involved in protein synthesis and cellular growth, such as MAPK and PI3K/Akt/S6K pathways. VKRs are not present in vertebrates, nor in some invertebrate species. Questions remain open about the origin of this little-known RTK family in evolution and its role in emergence and specialization of Metazoa. What is the meaning of maintenance or loss of VKR in some phyla or species in terms of development and physiological functions? The presence of VKRs in invertebrates of economical and medical importance, such as pests, vectors of pathogens and platyhelminth parasites, and the implication of these RTKs in gametogenesis and reproduction processes are valuable reasons to consider VKRs as interesting targets in new programs for eradication/ control of pests and infectious diseases, with the main advantage in the case of parasite targeting that VKR counterparts are absent from the vertebrate host kinase panel.